The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fphar.2022.877932
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Induced Neutropenia in Pediatric Patients: New Insights From Pharmacoepidemiological Analyses and a Systematic Review

Abstract: Aim: to characterize pediatric cases of antibiotic-associated neutropenia through a multidisciplinary approach, focusing on the temporal association between the wide spectrum of treatment options and the occurrence of this relatively uncommon but potentially clinically relevant adverse event.Methods: we carried out a pharmacoepidemiological analysis based on the FDA Adverse Event Reporting System (FAERS) database, a retrospective chart review and a systematic review of the literature, focusing on the time to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
3
2
0
Order By: Relevance
“…We identified associations between neutropenia and the total length of antibiotic therapy, length of intravenous antibiotic therapy, length of admission to the hospital and admission to the intensive care unit (Table 2) . Previous reports concur with the increased risk of neutropenia with longer treatment courses, as we saw in our cohort 33,34 . While standard intravenous and oral dosing for many common antibiotics (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…We identified associations between neutropenia and the total length of antibiotic therapy, length of intravenous antibiotic therapy, length of admission to the hospital and admission to the intensive care unit (Table 2) . Previous reports concur with the increased risk of neutropenia with longer treatment courses, as we saw in our cohort 33,34 . While standard intravenous and oral dosing for many common antibiotics (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…17 The congenital and cyclic categories are regarded as congenital neutropenia, while the idiopathic and autoimmune categories are acquired. In Present Study, the frequency of Non-Malignant Neutropenia was found to be 0.83% which was slightly lesser but still comparable with other studies like Battini et al (1.91%), 9 Jiunn-Ming Sheen et al (2.16%), 12 Kyriaki Karavanaki et al (2%). 11 Females were more than males, while in other studies of Joanna Konieczek et al, 18 Tschenin et al, 19 and Akanksha Mahajan et al 19 Present Study shows the mean hemoglobin level is 7.8g/dl whereas Vasiliki Vlacha et al 6 and Ozdemir et al 13 have higher mean hemoglobin level.…”
Section: Discussionsupporting
confidence: 89%
“…85.7% patients belonged to>2 years of age group which is comparable with Nguyen S.N et al10 while in study of Jiunn-Ming Sheen et al12 and Kyriaki Karavanaki et al 11 majority patients were below 1 year of age. In Present Study, mean age of the cases is more than 5 years which is comparable with Vasiliki Vlacha et al6 and Battini et al9 In Nguyen S.N et al,10 Kyriaki Karavanaki et al11 and Jiunn-Ming Sheen et al12 mean age of the cases is less than 5 years.In Present Study, 95.2% patients were residing at urban area, on counterpart, Nguyen S.N et al10 study 33.02% patients were residing at urban area. More cases belonging to urban region in the present study can be because of the urban location of the hospital in tier 2 city.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Other studies have reported associations between linezolid and specific side effects using centralized data (Lee and Caffrey, 2018;Dai et al, 2020;Gatti et al, 2021a;Battini et al, 2022;Ni et al, 2022;Shao et al, 2023). This study, for the first time, comprehensively documented and evaluated the safety of post-marketing administration of linezolid based on the largest sample of realworld data to date.…”
Section: Tto Analysismentioning
confidence: 99%